P249 Predictors of adverse outcome in sarcoidosis complicated by chronic pulmonary aspergillosis. (20th September 2022) - Nwankwo, Lisa; Periselneris, Jimstan; Gilmartin, Desmond; Desai, Sujal; Shah, Anand; Kouranos, Vasilis; Renzoni, Elisabetta; Wells, Athol; Molyneaux, Phil; George, Peter; Kokosi, M.; Devaraj, Anand; et al.
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Introduction: Aspergillosis complicating pulmonary sarcoidosis is associated with high mortality. 1 The specific prognostic impact of fibrocavitary sarcoid disease, however, remains poorly understood. A better understanding of the factors that determine adverse outcomes in such patients may improve the management of both the underlying sarcoid disease and associated secondary fungal infection. Methods: We implemented a clinical informatics pipeline to data-mine the hospital's clinical data warehouse and identify patients for inclusion in this study. Cases of pulmonary sarcoidosis with elevated Aspergillus IgG (>40 mgA/l) presenting between January 2009 and March 2021 were retrospectively identified. Controls (sarcoidosis with normal Aspergillus IgG titer) were case matched by baseline percentage-predicted gas transfer factor (TLco; ±5% variance). CPA cases were identified by using ISHAM criteria for diagnosing CPA, that is Aspergillus IgG >40 mgA/l plus keyword search for cavities or fungal ball in the CT reports based on search terms for aspergilloma, cavity, intra-cavitary, and mycetoma. Computed tomography (CT), baseline lung function, and survival data were analyzed. Results: Among 179 cases (high Aspergillus IgG) and 477 controls (normal Aspergillus IgG), no inter-group difference was evident in the median age at presentation [48 (IQR 40-58) vs 50 (IQR 42-59)] or gender (proportion female: 45.5% vs 51.1%). Amongst the cases, 80/179 (45%) had fibrocavitary changes, compared with 14/477 (2.9%) of the controls ( P <.001). Radiologically-evident aspergilloma was present in 80% (64/80) of the cases with fibrocavitary sarcoidosis. Evidence of fibrocavitary destruction was associated with higher overall mortality (60% vs 9.1% in the non-fibrocavitary subgroup; <.0001), and poorer median survival (Fig. 1). The median age at death was lower where there was fibrocavitary disease, and even lower with high Aspergillus IgG, and this was statistically significant. These cases also had poorer lung function compared to non-fibrocavitary disease (Fig. 2): mean %-predicted forced vital capacity (FVC) 71.3% vs 91.4% ( P <.0001), and in the controls: 69.9% vs 86.0% ( P <.01). A similar trend was observed in %-predicted TLco amongst the fibrocavitary cases: 45.8% vs 64.2% non-fibrocavitary ( P <.0001) and in the fibrocavitary controls: 39.7% vs 59.0% non-fibrocavitary ( P <.0001). Comparing only those with fibrocavitation, neither the percentage-predicted FVC (71.3% vs 69.9% predicted; P = .82) nor the percentage-predicted TLco (45.7% and 39.7% predicted; P = .16) differed between cases and controls. Conclusions: Fibrocavitary sarcoidosis is associated with worse lung function and poorer median survival. In this group, elevated Aspergillus IgG highlights a greater incidence of aspergilloma. Implications: Fibrotic transformation of pulmonary sarcoidosis heightens symptom burden, predisposes to chronic Aspergillus infection, and is prognostically important particularly when there is supervening fibrocavitary lung destruction. Sensitive stratification of such patients for the long-term outcomes may help identify particular individuals for earlier and more focused therapeutic intervention. Sources: Uzunhan et al ., Chronic pulmonary aspergillosis complicating sarcoidosis, European Respiratory Journal 2017 49: 1 602 396; DOI: 10.1183/13993003.02396-2016